Impact of Long-term Manures and Balanced Fertilization on Soil Carbon Pools in Mollisols under Rice-Wheat Cropping System - Mohd. Yaseen (Journal of the Indian Society of Soil Science, 2022)
This paper assesses the impact of long-term (30 years) application of balanced fertilizers with or without farmyard manure (FYM) on soil carbon pools after harvest of rice under intensively cultivated rice-wheat cropping system. Soil organic carbon (SOC) and its fractions were evaluated in soil (Aquic Hapludoll with silty loam) during 2014-15 from an ongoing long-term field experiment (LTFE) initiated in 1984 at Crop Research Centre of Govind Ballabh Pant University of Agriculture and Technology, Pantnagar. Fourteen fertilization treatments with different levels of nitrogen (N), phosphorus (P), potassium (K), with or without FYM and zinc (Zn) were arranged in a randomized block design. Findings of investigation revealed that application of 100% NPK (N120+P40+K40) and super optimal NPK (N180+P80+K40) along with FYM and Zn increased SOC by 51.5 and 58.7 per cent, particulate organic C by 41.4 and 45.4 per cent, water soluble C by 77.9 and 86.4 per cent, hot water extractable C by 91.2 and 97.1 per cent, water soluble carbohydrates by 187.3 and 204.9 per cent, potentially mineralizable C by 107.6 and 114.5 per cent, KMnO4 oxidizable C by 43.1 and 47.0 per cent and microbial biomass C by 66.3 and 64.4% over control in entire 0-60 cm soil profile, respectively. It was also found that rice grain yield was increased by 222.2 per cent over control with the application of 100% NPK (N120+P40+K40) along with FYM and Zn. Therefore, from this experiment it is concluded that application of balanced optimal and super optimal NPK along with FYM and Zn (N120+P40+K40+Zn+FYM and N180+P80+K40+Zn+FYM) in intensively cultivated cropping system is a sustainable management practice to sustain soil fertility by accumulating and sequestering sizable carbon in soil and enhanced production of rice-wheat cropping system.